Praktik Kepemimpinan Perempuan pada UMKM dalam Meningkatkan Kinerja Karyawan - Intan Tenisia Prawita Sari; Mohamad Iqbal Abdul Rauf; Ernawati (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
Women's leadership has become increasingly important in the development of micro, small, and medium-sized enterprises (MSMEs). However, previous studies have primarily focused on leaders' characteristics and organizational outcomes, while limited attention has been given to women's leadership practices as perceived by employees. This study aims to examine the relationship between women's leadership practices and employee performance in MSMEs. A quantitative approach was employed using a survey of 81 employees working under female leaders in an Indonesian MSME. Data were collected through structured questionnaires and analyzed using multiple linear regression. The results indicate that women's leadership practices have a positive and significant relationship with employee performance. Leadership practices characterized by clear direction, effective coordination, openness to employee input, appropriate delegation of responsibilities, and employee involvement in problem-solving contribute to higher employee performance. These findings contribute to the leadership literature by shifting the focus from female leaders as individuals to **female leadership practices perceived by employees, offering a more comprehensive understanding of women's leadership in the MSME context. Practically, the findings highlight the importance of strengthening participative leadership practices to improve employee performance and organizational effectiveness.